Implementation of Good Tourism Governance Based on Local Wisdom in Increasing Community Income in the Simanindo Samosir Tourism Village, North Sumatra - Revida, Erika; Badaruddin (Talenta Publisher, 2024)
Good tourism governance based on local wisdom is the management of tourist villages carried out based on the principles of participation, accountability and evaluation based on cultural values that grow and develop in society, such as mutual trust, mutual support, mutual cooperation and so on. The method of activity carried out in this community service is socialization, training, simulation and mentoring for several days to the community and tourism awareness groups in the Simanindo Samosir tourist village, North Sumatra so that there is an increase in knowledge, attitudes, skills and behavior of tourism awareness group administrators. and society and society and apply the concepts that have been presented in the training. The results of the activities carried out showed that the Simanindo tourist village community and village officials as well as tourism awareness groups seemed enthusiastic about listening to and following the event until it was finished and committed to implementing it. On the first day, the venue is mapped and the technicalities of the event are discussed, the event rundown and who will be invited the following day. On the second day it was held from 14 to 18, accompanied by lectures, questions and answers and long discussions. Thus, it can be concluded that community service activities have received a positive response and we hope that similar activities can be carried out in the future. This community service was closed with a group photo and distributing